The Role Of Family in Shaping Social Values in the Digital Era - Khaeriyah Khaeriyah; Nurasia Natsir (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study explores the vital role of families in shaping social values among children and adolescents within the increasingly dominant digital environment. Digital technology has transformed communication patterns and modes of cultural transmission, presenting new challenges for families in instilling core values while navigating technological influences. Using a qualitative case study approach, this research involved 15 Indonesian families from diverse socioeconomic backgrounds. Data collection methods included in-depth interviews, observations, and media diaries to understand the dynamics of value transmission in digital contexts.The findings reveal that family communication patterns—whether conversation-oriented, conformity-oriented, or laissez-faire—significantly influence children’s internalization of values. Effective strategies identified include parental digital co-learning, value-based guidance, and the promotion of critical media literacy. Major challenges include value conflicts between family teachings and digital culture, concerns over cultural preservation, and competition for children’s attention due to immersive technology.Nevertheless, the study also found that families can strategically leverage technology to reinforce values through careful media selection, engagement in meaningful digital activities, and fostering intergenerational connections. In conclusion, while families remain crucial socializing agents, the successful transmission of values requires thoughtful adaptation of traditional practices to meet the realities of the digital age.